Mapping the nursing competences in neonatology: a qualitative research - Alfieri, Emanuela; Alebbi, Alessia; Bedini, M. Giovanna; Boni, Laura; Foà, Chiara (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: There are several studies that support the importance of advanced expertise and specialization of the neonatal pediatric nurse. However, proceeding with a analysis of the scientific literature regarding the nursing advanced competence in neonatology, very few studies specify and define these competences. The aim of the study is investigate and analyze skills, tasks and responsibilities of the neonatal pediatric nurse, to map a “neonatal nurse competence profile”, offered from the points of view of the Neonatology Units professionals. Methods: 32 professionals (nurses, physicians, psychologists, healthcare assistants) operating in the Neonatal Intensive Care Unit of two Italian Hospitals were interviewed. The semi-structured interviews have been performed, transcribed and analyzed following the Levati’s model (based on Activity, Expectations and Evaluation system). Results: About the nurses activities, the participants underlined the newborn care, the care of the caregiver and the “bureaucratic” activities. About the system of expectations, the participants marked on specific skills but those are described only comprehensively. About the evaluation system there are different perceptions among the professionals, but the nurses themselves feel that they have to answer for their actions primarily to infants and families, indicating a sense of responsibility towards the patients. Conclusions: On the basis of the interviews a profile of a neonatal nurse competences has been drawn up. This consists of 42 competences that future studies can further specify, integrate and expand.